2022
DOI: 10.3389/fnut.2022.850689
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Induces Pulmonary Fibrotic Phenotype Through Promoting Epithelial-Mesenchymal Transition Mediated by ROS-Activated Latent TGF-β1

Abstract: Fructose is a commonly used food additive and has many adverse effects on human health, but it is unclear whether fructose impacts pulmonary fibrosis. TGF-β1, a potent fibrotic inducer, is produced as latent complexes by various cells, including alveolar epithelial cells, macrophages, and fibroblasts, and must be activated by many factors such as reactive oxygen species (ROS). This study explored the impact of fructose on pulmonary fibrotic phenotype and epithelial-mesenchymal transition (EMT) using lung epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The evidence indicates that fructose can modulate mTORC1 activity in several tissues. Only one study, on idiopathic pulmonary fibrosis, has shown that fructose can indirectly promote fibrosis through the stimulation of latent TGFβ1 in human epithelial cells [ 150 ]. However, there are no reports about the effect of fructose in lung tissue ( Figure 2 b).…”
Section: Activation Of Mtor Signaling In Lung Function and Chronic Hi...mentioning
confidence: 99%
“…The evidence indicates that fructose can modulate mTORC1 activity in several tissues. Only one study, on idiopathic pulmonary fibrosis, has shown that fructose can indirectly promote fibrosis through the stimulation of latent TGFβ1 in human epithelial cells [ 150 ]. However, there are no reports about the effect of fructose in lung tissue ( Figure 2 b).…”
Section: Activation Of Mtor Signaling In Lung Function and Chronic Hi...mentioning
confidence: 99%